Treatment of thyrotoxicosis - Delgado, Bolívar (Cirugía del Uruguay, 1996)
In a series of 53 patients operated far thyrotoxicosis in recent years, the authors analyse in retrospectiva: etiology, /ength of preoperative therapy, indication for surgica/ therapy, most frequently performed operations, postoperative complications (special/y hypoparathyroidism and vocal cords para/ysis), fol/ow-up with special emphasis on relapses and hypothyroidism and last of ali mortality These data were compared to those of international bibliography